Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 336147 species occurrences available in GBIF matching the query: { "and" : [ "Country is Japan", "License is CC0 1.0" ] } The dataset includes 336147 records from 239 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0041041-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences